Information security essentials a guide for reporters, editors, and newsroom leaders - McGregor, Susan E. (Columbia University Press, 2021)
"In the nearly seven years since the Snowden revelations, information security concerns for news organizations and members of the press have only intensified worldwide. In the United States, a record-breaking number of whistleblower prosecutions under the Obama administration has been followed by outright aggression towards the press from the Trump presidency. Globally, information requests, imprisonment, and surveillance of journalists are at an all-time high. In Information Security Essentials, Susan McGregor provides an accurate and accessible understanding of the key issues and approaches for thinking about and building information security into journalistic practice. Aimed at students, working journalists, and media organizations, the book lays out the principles of information security that will allow journalists to undertake important and, at times, risky work. McGregor builds on years of original academic research, interviews with dozens of journalists, editors and information security experts, and first-hand experience with the tools and techniques described. The book serves both as an introduction and reference for anyone wishing to improve the security of their information and information-gathering in order to protect themselves, their colleagues, their sources, and their stories. Topics discuss include the legal and technological contexts of information security, threat modeling and attack trees, working internationally, developing an institutional culture of security, the impact of misinformation, and online harassment"--